The effect of particle size of wollastonite filler on thermal performance of intumescent fire retardant coating - Zia-Ul-Mustafa, M. (EDP Sciences, 2014)
Intumescent Fire retardant coatings (IFRC's) are one of the simplest ways to protect substrates exposed to fire. In this study, Wollastonite (W) filler of two different particle sizes were used to determine the fire performance of intumescent fire retardant coating. The basic ingredients of the coating were ammonium poly-phosphate (APP) as acid source, expandable graphite (EG) as carbon source, melamine (MEL) as blowing agent in epoxy binder, boric acid as additive and hardener as curing agent. A series of coating formulations were developed by using different weight percentages of both sized Wollastonite fillers. The coated steel substrate samples were tested for fire performance using Bunsen burner and char expansion was measured using furnace fire test. A Comparison of the coatings thermal performance was determined. Wollastonite containing filler particle size 10 Î¼m showed better thermal performance than formulations containing filler's particle size 44 Î¼m. Â© 2014 Owned by the authors, published by EDP Sciences.